(untitled) (Journal of Hama University, 2026)
This study aimed to establish a relationship between the maximum smile width and the occlusal vertical dimension, and to add a new parameter that would help obtain a similar ratio or measure for the occlusal vertical dimension. Research Materials and Methods: The research sample consisted of 40 male and female students from the Faculty of Dentistry at Hama University. The students were divided into two main groups, equal in gender, and measurements were taken using an electronic scale. Results: This study demonstrated a statistically significant linear correlation between the values of the occlusal vertical dimension (in mm) and the values of the maximum smile width (in mm). Conclusions: Within the limits of this research, and based on the results we obtained, we can conclude the following: 1. There is a direct relationship between the occlusal vertical dimension and the maximum smile width among individuals with complete natural teeth in Syrian society, and this relationship can be reliably determined. 2. Patient gender does not affect the determination of the occlusal vertical dimension in individuals with complete natural teeth, as the maximum smile width measurement was reliable for both males and females